One Decade of Environmental Disasters in Brazil: The Action of Veterinary Rescue Teams - Sássi, Carla; Carvalho, Gabriel Domingos; de Castro, Leonardo Maggio; Junior, Cláudio Zago; Nunes, Vânia de Fátima Plaza; do Nascimento, Arthur Augusto Tavares; Bastos, Ana Liz Ferreira; Santana, Luciana Guimarães; Gonçalves, Ilka do Nascimento (Frontiers in Public Health, 2021)
Into the interdisciplinary concept of One Health, EcoHealth and Planetary Health, this paper focuses on participatory knowledge-to-action approaches by the relate of one decade of environmental disasters in Brazil and the action of veterinary rescue teams in goal to give support for future disaster preparedness. This paper will present the historic of the acting of the rescuing animal teams that are victims of environmental disaster situations, in addition to addressing the need for contingency plans and response management in these types of events. The main events with the participation of veterinary rescue teams in the Brazilian States were, chronologically: 2011 - flood and landslide (RJ); 2012 – flood (AC, MG, PA); 2015 - dam break (MG); 2017 - flood (MG) and forest fire (MG, GO); 2019 - dam break and evacuation (MG) and flood (BA); 2020 - flood (ES, MG) and forest fires (MT, MS). The Brazilian disasters that had a large global repercussion were the ruptures of ore dams in Marina (2015) and Brumadinho (2019), both in the State of Minas Gerais. The role of veterinarians in these events was recognized by the Federal Council of Veterinary Medicine (CFMV) after their performance in Mariana-MG (2015) and in 2020 the CFMV approved the National Mass Disaster Contingency Plan Involving Animals. The work of veterinarians in interaction with other professionals in environmental disasters proved to be effective and necessary for the rescue of animals and to planning and to give support for disaster preparedness in the future.